1964
DOI: 10.1139/p64-204
|View full text |Cite
|
Sign up to set email alerts
|

On the Theory of Diffusion in a Magnetic Field

Abstract: Diffusion in the weakly paramagnetic aluminum (rich) – copper system has been investigated in a magnetic field. Aluminum – aluminum/3% copper solid diffusion couples were diffusion annealed in a magnetic field of 30 and 20 kilo-oersteds, and then analyzed for diffusion using a microhardness technique. A statistically significant 25% decrease in the diffusivity was found for the couples annealed in a 30-kilo-oersted field applied perpendicular to the diffusion direction. However, from the accuracy of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 13 publications
4
37
0
Order By: Relevance
“…Among these transformations, diffusion is very important in diffusional transformations, but there have been very few studies on the effects of a magnetic field on diffusion. Youdelis et al [65] reported that a magnetic field of 3 T suppressed the diffusivity of Cu in Al perpendicular to the direction of the field by about 25%. Now ever, Nakajima et al [66] did not find any effect of a magnetic field on the diffusion of Ni in Ti.…”
Section: Other Transformations In a Magnetic Fieldmentioning
confidence: 99%
“…Among these transformations, diffusion is very important in diffusional transformations, but there have been very few studies on the effects of a magnetic field on diffusion. Youdelis et al [65] reported that a magnetic field of 3 T suppressed the diffusivity of Cu in Al perpendicular to the direction of the field by about 25%. Now ever, Nakajima et al [66] did not find any effect of a magnetic field on the diffusion of Ni in Ti.…”
Section: Other Transformations In a Magnetic Fieldmentioning
confidence: 99%
“…Youdelis et al 1) reported that a 3 T magnetic field retarded the diffusion of copper in aluminium. Nakajima et al 2) observed no magnetic effects on the diffusion of nickel in titanium.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of static magnetic field on the diffusion behavior was firstly studied by Youdelis et al [10,11], who found diffusion suppression caused by static magnetic field and later by Nakajima et al [12], who, on the contrary, did not observe such effects. A shortcoming in their study is that the magnetic * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%